Multi-Mode Yagi Uda Patch Array Antenna With Non-Linear Inter-Parasitic Element Spacing - ISA, SITI RAHENA; JUSOH, MUZAMMIL; THENNARASAN SABAPATHY, THENNARASAN SABAPATHY; KAMARUDIN, MUHAMMAD RAMLEE; OSMAN, MOHAMED NASRUN; AKRAM ALOMAINY, AKRAM ALOMAINY (Ieee Acces, 2023)
A low-profile and broad steerable patch array antenna is presented. The improvement of the multi-directional functions from the broadside is very limited for the patch array antenna. In this work, the number of directional beams is enhanced by 40% using a novel approach, inter-parasitic element expansion technique and adopted only four PIN diode switches. Results in simulation and measurement have verified that the patch parasitic array antenna is capable -of generating seven beam patterns directed towards - 52◦ , -30◦ , -10◦ , 0◦ , +10◦ , +30◦ , and +52◦ at the xz-plane. Applying the inter-parasitic element spacing’s optimization and minimizing the switching circuitry using four RF PIN diodes on the parasitic elements have contributed to the gain achievement of more than 7 dBi.